KERJASAMA ANTAR DESA DALAM PEMBANGUNAN KAWASAN PERDESAAN - Bhudianto, Wahyu (Transformasi, 2014)
Development of Rural Regions is a combination of inter-village development in one (1)District /City. Development of Rural Regions implemented in an effort to speed up and improve the qualityof care, development, and empowerment of village communities in Rural Areas throughparticipatory development approach. development of cooperation between villages in rural areasof development, it is necessary to formulate a concept of sustainable development of rural areas.In the sustainable management of rural areas, there are four pillars or attributes. First,improving the quality of rural human resources(community empowerment). Second, improvingthe quality of rural infrastructure (infrastructure improvement). Third, improving the quality ofsocial and economic life (economic livelihood improvement). As well as the fourth, improving thequality of the local environment and cultural heritage(conservation and cultural preservation).Keywords: Village, Cooperation, Development